P58 Advance care planning in glioblastoma patients: development of a disease-specific ACP program. Issue Volume 9: Issue (2019)Supplement 2 (3rd December 2019) - Fritz, L; Zwinkels, H; Koekkoek, J; Reijneveld, J; Vos, M; Dirven, L; Pasman, R; Taphoorn, M
Abstract : Background: It is unknown if implementation of an Advance Care Planning (ACP) program is feasible in daily clinical practice for glioblastoma patients. We aimed to develop an ACP program, and assessed the preferred content, the best time to introduce such a program in the disease trajectory, and possible barriers and facilitators for participation and implementation. Methods: A focus group with health care professionals (HCPs) as well as individual semi-structured interviews with patients and proxies (of both living and deceased patients) were conducted. Results: All predefined topics were considered relevant by participants, including the current situation, worries and fears, (supportive) treatment options, and preferred place of care/death. Although HCPs and proxies of deceased patients indicated that the program should be implemented relatively early in the disease trajectory, patient-proxy dyads were more ambiguous. Several patient-proxy dyads indicated that the program should be initiated later in the disease trajectory. If introduced early, topics about the end-of-life should be postponed. A frequently mentioned barrier for participation was that the program would be confronting, while a facilitator included access to information. Conclusion: This study resulted in an ACP program specifically for glioblastoma patients. Although participants agreed on the content of the program, the optimal timing of introducing such a program was a matter of debate. Our solution is to offer the program shortly after diagnosis, but let patients and proxies decide which topics they want to discuss. The impact of the program on several patient- and care-related outcomes will be evaluated in a next step.